2022
DOI: 10.1155/2022/1451193
|View full text |Cite
|
Sign up to set email alerts
|

Potential Differences in the Cardiometabolic Risk Profile of Patients with Psoriatic Disease according to Their HLA-C 06 Status

Abstract: The human leukocyte antigen-C ∗ 06 (HLA-C ∗ 06, formerly HLA-Cw6) is the main genetic biomarker in psoriatic disease. It has been related to several phenotypic traits in psoriatic disease, but its role in relation to cardiometabolic comorbidities is unknown at present. Here, we analyze the potential connections between this biomarker and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…Many studies on psoriasis cardiometabolic comorbidities have focused mainly on its relationship with the HLA-C*06:02 allele. HLA-C*06:02-positive status is often associated with lower central adiposity, lower incidence of hypertension, and a lower prevalence of other cardiometabolic comorbidities (30,34,35). These are all consistent with our HLA-C*06:02 results which were found to be protective against high blood pressure and high cholesterol.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies on psoriasis cardiometabolic comorbidities have focused mainly on its relationship with the HLA-C*06:02 allele. HLA-C*06:02-positive status is often associated with lower central adiposity, lower incidence of hypertension, and a lower prevalence of other cardiometabolic comorbidities (30,34,35). These are all consistent with our HLA-C*06:02 results which were found to be protective against high blood pressure and high cholesterol.…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study by our group, we had detected a cardiometabolic endotype linked to HLA-Cw6 [4]. However, that study was carried out for clinical phenotyping purposes (in fact, the characterization of the PsA population was much finer), while the present cohort was constructed for genotyping studies, so the collection of variables was much more selective and exhaustive (for example, in the first cohort no information on fatty liver disease was collected, while in the cohort of the present study it was).…”
Section: Discussionmentioning
confidence: 87%
“…In fact, at least two recent independent studies carried out in populations of European Caucasian ancestry have found associations between HLA-Cw6 and a smaller waist circumference, less visceral adiposity, and, in general, a "protective" tendency against the development of certain CV risk factors such as hypertension. Thus, in these studies, the reduction in the risk of hypertension conferred by HLA-Cw6 has been around 30% [4,5]. A study carried out in a Spanish population also found a reducing effect of HLA-Cw6 on the risk of liver fibrosis in subjects with PsA, while curiously enough, the presence of hypertension increased this risk [7].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations